Flexural Strength of Reinforced Concrete RAC Beams Exposed to 6-hour Fire – Part 2: Rich Mix - Buller, A. H.; Oad, M.; Memon, B. A. (Engineering, Technology & Applied Science Research, 2019)
In this research work, experimental investigation on flexural strength of reinforced concrete beams exposed to fire for 6-hours at the temperature of 1000˚C is presented. The beams are made with 50% replacement of natural coarse aggregates with recyclable concrete aggregates. A total of 12 reinforced concrete beams using 1:1.5:3 mix (rich mix) and 0.54 water-cement ratio were cast. The beams were prepared in two groups. Group 1 beams were prepared with 50% recyclable aggregates, whereas group 2 beams were cast with all-natural aggregates (control specimens). All beams were exposed to fire at the above-mentioned temperature followed by testing in universal load testing machine under central point load. Comparison of the results reveals that proposed beams show comparable resistance even after exposed to 6-hours fire at 1000°C.